Roman kahramanı 'At'lar: Cahil, Gülsarı, Dorukısrak ve Dilara - (:unkn) unknown (My University, 2009)
“At”ın Türk kültüründeki yeri tartışılmayacak kadar önemlidir. Tarihinin önemli bir bölümünde Türklerin göçer hayat yaşadıkları düşünüldüğünde bunun şaşırtıcı bir tarafı yoktur. Nitekim hâlâ bozkırlarda ve dağlık bölgelerde yaşayan Türk asıllı halkların hayatındaki önemi devam etmektedir. At, aynı zamanda kültürün de parçasıdır. At üzerinde oynanan cirit oyunun Anadolu'da devam etmesi gibi, Türkistan ve Güney Türkistan coğrafyasında yaşayan Türk asıllı halklar arasında da “buzkaşı” veya daha yaygın bilinen adıyla “kökpar” oyunu canlılığını korumaktadır. Bu çalışmada, Anadolu, Kırgızistan, Kırım ve Güney Türkistan coğrafyasında yaşayan halkların kültüründe kendine yer edinmiş atların romanlara aksedişi incelenmiştir. Dört roman ele alınmış ve bu dört romandaki atlar üzerine değerlendirmeler yapılmıştır.

The importance of horse/s within the Turkic cultural has been and still is undisputable. This should not surprising for those who see the fact that the Turks throughout their history followed nomadic or semi-nomadic life style. In fact, among those Turkic people who live in the steppes and around mountains it is still part of their daily life styles. Just like the “Cirit” game survives in some places of Anatolia, the “buzkasi” or “kokpar” tradition still lives in Turkistan or in the Southern Turkistan among Turkic people. This study searches the reflection of horse/s within four novels represanting Anatolia, Kirgizstan, Crimea, and the Southern Turkistan so called Afghanistan. Four novels are looked through and made some evaluations on horses and their importance within the novels as well as within daily lives.
Horses as protagonists: Cahil, Gülsarı, Dorukısrak and Dilara
Keywords: Kültürel Çalışmalar; Folklor